Best Answer

2x > -6 and x - 4 < 3

x + 3 > 2x + 1 and -4x < -8

-6 < x + 3 < 6

-3x > -6 or x - 5 < 2

x - 2 > 2x + 1 or 10 > -2x + 2

can someone please help me!

Q: 2x -6 and x - 4 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

# ## 2x > -6 and x - 4 < 3 ## x + 3 > 2x + 1 and -4x < -8 ## -6 < x + 3 < 6 ## -3x > -6 or x - 5 < 2 ## x - 2 > 2x + 1 or 10 > -2x + 2

What is the answer to the problem 2x > -6 and x - 4 < 3 = x > 1

3x + 4 = x + 6 2x + 4 = 6 2x = 2 x = 1 Check it. 3 + 4 = 1 + 6 It checks.

2x+3=3x-3 2x-3x=-3-3 -x=-6 x=6

(4 + 2x) - (-2x + 1) = 13 + 6 4 + 2x + 2x -1 = 19 4x +3 = 19 4x = 19 - 3 4x = 16 therefore x = 16/4 x = 4

Related questions

# ## 2x > -6 and x - 4 < 3 ## x + 3 > 2x + 1 and -4x < -8 ## -6 < x + 3 < 6 ## -3x > -6 or x - 5 < 2 ## x - 2 > 2x + 1 or 10 > -2x + 2

4 - 2x = 10 -2x = 10-4 -2x = 6 -x = 3 x = -3

4

What is the answer to the problem 2x > -6 and x - 4 < 3 = x > 1

3x + 4 = x + 6 2x + 4 = 6 2x = 2 x = 1 Check it. 3 + 4 = 1 + 6 It checks.

2x+3=3x-3 2x-3x=-3-3 -x=-6 x=6

within the equation 2x-3*4 you have 2x-12 but if you brake it down more you will have x= -6

I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.

2x + 4 = 10 2x = 10 - 4 = 6 2x = 6 x = 6/2 = 3

(4*x*3)/2x=12x/2x=6

-4

2x/3=6 =6-3=3 x= 2+2=4/3 is 4upon3